EVALUASI GAYA KEPEMIMPINAN DAN SISTEM PENGENDALIAN MANAJEMEN BERBASIS FAMILINESS PADA PERUSAHAAN CV. JASINDO ELEKTRONIK - Muhamad Indra Sentosa (Perpustakaan Universitas Surabaya, 2018)
Abstract – The purpose of this research is to learn how the management control system has been applied in CV. Jasindo Elektronik company. The objective of this research is to evaluate the management control system weaknesses in the CV. Jasindo Elektronik company using Familiness perspective.This research is qualitative research with CV. Jasindo Elektronik as the object of the research The object of this research is just CV. Jasindo Elektronik without involving external sources. The collected data has been collected by interview and observation method with the time length 1 month. The findings indicate that CV. Jasindo Elektronik didn’t apply a formal management control system, too much depending on owner, and also CV. Jasindo Elektronik never build a culture on its company.CV. Jasindo Elektronik need familiness as the basic to build a company culture and formal management control system. The results of the research implying that combination between familiness and formal management control system positively affected the company for sustainability for family business in CV. Jasindo Elektronik.